(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
To reveal the main features of clinical-functional manifestations of vegetative dystonia at teenagers of 15-17 years due to their harmonic physical development. Research is executed according to the results of complex observation of young men - up to call-up age and conscripts in Andijan city at the age of 15-17 years called-up for joining Armed forces in 2009-2011 (n=571 teenagers). The following clinical and instrumental methods of research have been used: questionnaire, clinical observation, estimation of neuropsychiatric development, estimation of sexual development, somatometry, estimation of physical development level and fullness of harmony, somatoskopy .